Sialylation-dependent pharmacokinetics and differential complement pathway inhibition are hallmarks of CR1 activity in vivo. Issue 9 (13th May 2022) - Wymann, Sandra; Mischnik, Marcel; Leong, David; Ghosh, Subhajit; Tan, Xiahui; Cao, Helen; Kuehnemuth, Benjamin; Powers, Glenn A.; Halder, Partho; de Souza, Mitchell J.; James, Hannah S.; Tomasetig, Vesna; et al.
Abstract : Human Complement Receptor 1 (HuCR1) is a potent membrane-bound regulator of complement both in vitro and in vivo, acting via interaction with its ligands C3b and C4b. Soluble versions of HuCR1 have been described such as TP10, the recombinant full-length extracellular domain, and more recently CSL040, a truncated version lacking the C-terminal long homologous repeat domain D (LHR-D). However, the role of N-linked glycosylation in determining its pharmacokinetic (PK) and pharmacodynamic (PD) properties is only partly understood. We demonstrated a relationship between the asialo-N-glycan levels of CSL040 and its PK/PD properties in rats and non-human primates (NHPs), using recombinant CSL040 preparations with varying asialo-N-glycan levels. The clearance mechanism likely involves the asialoglycoprotein receptor (ASGR), as clearance of CSL040 with a high proportion of asialo-N-glycans was attenuated in vivo by co-administration of rats with asialofetuin, which saturates the ASGR. Biodistribution studies also showed CSL040 localization to the liver following systemic administration. Our studies uncovered differential PD effects by CSL040 on complement pathways, with extended inhibition in both rats and NHPs of the alternative pathway compared with the classical and lectin pathways that were not correlated with its PK profile. Further studies showed that this effect was dose dependent and observed with both CSL040 and the full-length extracellular domain of HuCR1. Taken together, our data suggests that sialylation optimization is an important consideration for developing HuCR1-based therapeutic candidates such as CSL040 with improved PK properties and shows that CSL040 has superior PK/PD responses compared with full-length soluble HuCR1.